Anterior cruciate ligament reconstruction with remnant preservation: current concepts. Issue 3 (16th April 2020) - Rothrauff, Benjamin B; Kondo, Eiji; Siebold, Rainer; Wang, Joon Ho; Yoon, Kyoung Ho; Fu, Freddie H
Abstract : Anterior cruciate ligament (ACL) tears are a common knee injury, and anatomic ACL reconstruction (ACLR) is now the standard of care to restore knee stability. Nevertheless, re-tear rates exceeding 5% are commonly reported, with an even higher percentage of patients unable to achieve preinjury knee function. As the torn ACL remnant contains elements (eg, cells, blood vessels and mechanoreceptors) essential to ACL function, it has been hypothesised that ACLR with remnant preservation may improve graft remodelling, in turn more quickly and completely restoring ACL structure and function. In this Current Concepts review, we summarise the present understanding of ACLR with remnant preservation, which includes selective bundle reconstruction of partial (one-bundle) ACL tears and single- and double-bundle ACLR with minimal to partial debridement of the torn ACL stump. Reported benefits of remnant preservation include accelerated graft revascularisation and remodelling, improved proprioception, decreased bone tunnel enlargement, individualised anatomic bone tunnel placement, improved objective knee stability and early mechanical support (with selective bundle reconstruction) to healing tissues. However, clinical studies of ACLR with remnant preservation are heterogeneous in the description of remnant characteristics and surgical technique. Presently, there is insufficient evidence to support the superiority of ACLR with remnant preservation over the standard technique. Future studies should better describe the ACL tear pattern, remnant volume, remnant quality and surgical technique. Progress made in understanding and applying remnant preservation may inform, and be reciprocally guided by, ongoing research on ACL repair. The goal of research on ACLR with remnant preservation is not only to achieve anatomic structural restoration of the ACL but also to facilitate biologic healing and regeneration to ensure a more robust and functional graft.